Impact of volcanic aerosols on stratospheric ozone recovery. Issue 17 (7th September 2017) - Naik, Vaishali; Horowitz, Larry W.; Daniel Schwarzkopf, M.; Lin, Meiyun
Abstract: We use transient GFDL‐CM3 chemistry‐climate model simulations over the 2006–2100 period to show how the influence of volcanic aerosols on the extent and timing of ozone recovery varies with (a) future greenhouse gas scenarios (Representative Concentration Pathway (RCP)4.5 and RCP8.5) and (b) halogen loading. Current understanding is that elevated volcanic aerosols reduce ozone under high halogen loading but increase ozone under low halogen loading when the chemistry is more NO x dominated. With extremely low aerosol loadings (designated here as "background"), global stratospheric ozone burden is simulated to return to 1980 levels around 2050 in the RCP8.5 scenario but remains below 1980 levels throughout the 21st century in the RCP4.5 scenario. In contrast, with elevated volcanic aerosols, ozone column recovers more quickly to 1980 levels, with recovery dates ranging from the mid‐2040s in RCP8.5 to the mid‐2050s to early 2070s in RCP4.5. The ozone response in both future emission scenarios increases with enhanced volcanic aerosols. By 2100, the 1980 baseline‐adjusted global stratospheric ozone column is projected to be 20–40% greater in RCP8.5 and 110–200% greater in RCP4.5 with elevated volcanic aerosols compared to simulations with the extremely low background aerosols. The weaker ozone enhancement at 2100 in RCP8.5 than in RCP4.5 in response to elevated volcanic aerosols is due to a factor of 2.5 greater methane in RCP8.5 compared with RCP4.5. Our results demonstrate the substantial uncertainties in stratospheric ozone projections and expected recovery dates induced by volcanic aerosol perturbations that need to be considered in future model ozone projections. Key Points: Increased volcanic aerosols, relative to extremely low background levels, indicate earlier ozone recovery under RCP4.5 and RCP8.5 scenarios Volcanic aerosols contribute to uncertainty in stratospheric ozone recovery Projections of stratospheric ozone should consider volcanic aerosols Plain Language Summary: Uncertainty in future levels of stratospheric aerosols from volcanic eruptions has been identified as a key uncertainty in predicting future stratospheric ozone abundance. We use transient GFDL‐CM3 chemistry‐climate model simulations over the 2006‐2100 time period to show how the influence of volcanic aerosols on the extent and timing of ozone recovery varies with (a) future greenhouse gas scenarios (RCP4.5 and RCP8.5) and (b) halogen loading. We show that increased volcanic aerosol abundances would lead to earlier ozone recovery under the RCP4.5 and RCP8.5 scenarios. Projections of stratospheric ozone should consider volcanic aerosols.